The role of a Sheikh Mohammad Khal in cultural & Kurdish Journalism )1939-1989( - Mohammed, Prof. Dr. Bahadin Ahmad (Sulaimani Journal for Humanities, 2023)
Kurdish cultural & media journal since the beginning and until modern century Have gone throng many ups and downs. For this cause many writers and cultured Kurds, especially teachers and religious scholars، raised of mosques and religious schools back them and now as well their impact in developing this field. One of those scholar، religious figure, writer and cultural figure in the last century was Sheikh Mohammad Khal (1904-1989). This research shows the role and attempts of Sheikh in cultural & Kurdish Journalism fields since (1939-1989) for this purpose he spent nearly (50) years of his life to write books in different categories in both Kurdish and Arabic apart from writing tenth of articles and journalism objects in both mentioned languages in Kurdish Magazines The importance of the research is that، it shows Sheikh Mohammad`s cultural and Journalism role between since (1939-1989) and though this aim of the research trying to identify his role in both fields in that time. The used method to do the research is the descriptive and historical method.
Keywords: role; Sheikh Mohammad Khal; Cultural; Kurdish Journalism